A review of blended learning approach at senior secondary level schools (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The use of blended learning strategies in senior secondary schools is examined in this paper, with a focus on how combining conventional in-person teaching with online resources might improve student learning results. Their use and effectiveness are evaluated for a variety of blended learning models, including Khan's Octagonal Framework and the K–12 models. The study also explores the psychological effects of blended learning, emphasizing how it might lower anxiety and promote positive attitudes about biology and other scientific courses. By examining important research and frameworks, the study draws attention to the advantages and disadvantages of this strategy and argues for its wider use in contemporary educational systems.